Gold(I)-catalyzed domino cyclization for the synthesis of polyaromatic heterocycles - Morin, Mathieu; Levesque, Patrick; Barriault, Louis (Beilstein Journal of Organic Chemistry, 2013)
Gold(I) complexes have emerged as powerful and useful catalysts for the formation of new C–C, C–O and C–N bonds. Taking advantage of the specificity of [IPrAuNCMe][SbF6] complexes to favor the 5-exo-dig cyclization over the 6-endo-dig pathway, we report a high yielding and efficient method to generate substituted polyaromatic heterocycles under remarkably mild reaction conditions.
Keywords: catalysis; cyclization; gold(I); gold catalysis; heterocycles; regioselectivity

(untitled) - Gorin, D. J.; Toste, F. D. (Nature, 2007)

(untitled) - Jiménez-Núñez, E.; Echavarren, A. M. (Chem. Commun., 2007)

(untitled) - Fürtsner, A.; Davies, P. W. (Angew. Chem., Int. Ed., 2007)

(untitled) - Hashmi, A. S. K. (Chem. Rev., 2007)

(untitled) - Gorin, D. J.; Sherry, B. D.; Toste, F. D. (Chem. Rev., 2008)

(untitled) - Li, Z.; Brouwer, C.; He, C. (Chem. Rev., 2008)

(untitled) - Arcadi, A. (Chem. Rev., 2008)

(untitled) - Skouta, R.; Li, C.-J. (Tetrahedron, 2008)

(untitled) - Shapiro, N. D.; Toste, F. D. (Synlett, 2010)

(untitled) - Wagner, W. A.; Auzias, M. (Angew. Chem., Int. Ed., 2011)

(untitled) - Watson, I. D. G.; Toste, F. D. (Chem. Sci., 2012)

(untitled) - Hashmi, A. S. K.; Rudolph, M. (Chem. Soc. Rev., 2008)

(untitled) - Barabé, F.; Levesque, P.; Korobkov, I.; Barriault, L. (Org. Lett., 2011)

(untitled) - Mauleón, P.; Zeldin, R. M.; González, A. Z.; Toste, F. D. (J. Am. Chem. Soc., 2009)

(untitled) - Benitez, D.; Shapiro, N. D.; Tkatchouk, E.; Wang, Y.; Goddard, W. A., III; Toste, F. D. (Nat. Chem., 2009)

(untitled) - Alcarazo, M.; Stork, T.; Anoop, A.; Thiel, W.; Fürstner, A. (Angew. Chem., Int. Ed., 2010)

(untitled) - Benitez, D.; Tkatchouk, E.; Gonzalez, A. Z.; Goddard, W. A., III; Toste, F. D. (Org. Lett., 2009)

(untitled) - Barabé, F.; Levesque, P.; Sow, B.; Bellavance, G.; Bétournay, G.; Barriault, L. (Pure Appl. Chem., 2013)

(untitled) - de Frémont, P.; Scott, N. M.; Stevens, E. D.; Nolan, S. P. (Organometallics, 2005)

(untitled) - Nieto-Oberhuber, C.; López, S.; Echavarren, A. M. (J. Am. Chem. Soc., 2005)

(untitled) - Nieto-Oberhuber, C.; Pérez-Galán, P.; Herrero-Gómez, E.; Lauterbach, T.; Rodriguez, C.; López, S.; Bour, C.; Rosellón, A.; Cárdenas, D. J.; Echavarren, A. M. (J. Am. Chem. Soc., 2008)

(untitled) - Yeh, M.-C. P.; Tsao, W.-C.; Lee, B.-J.; Lin, T.-L. (Organometallics, 2008)

(untitled) - Pérez-Galán, P.; Martin, N. J. A.; Campaña, A.; Cárdenas, D. J.; Echavarren, A. M. (Chem.–Asian J., 2011)

(untitled) - Dateer, R. B.; Shaibu, B. S.; Liu, R.-S. (Angew. Chem., Int. Ed., 2012)

(untitled) - Brazeau, J.-F.; Zhang, S.; Colomer, I.; Corkey, B. K.; Toste, F. D. (J. Am. Chem. Soc., 2012)

(untitled) - Bohlmann, F.; Ziesche, J.; King, R. M.; Robinson, H. (Phytochemistry, 1980)

(untitled) - Goodwin, S.; Smith, A. F.; Horning, E. C. (J. Am. Chem. Soc., 1959)

(untitled) - Miller, M. C.; McCarthy, F. O. (RSC Adv., 2012)